Trophic spectrum of Tadarida brasiliensis (Chiroptera: Molossidae) in the southeaster Buenos Aires Province, Argentina - Olmedo, María Luz (2021)
Tadarida brasiliensis is one of the most important arthropodophagous bats in the control of agricultural pests. However, its food habits are poorly studied in Argentina. The aim of this work was to analyze the diet composition of T. brasiliensis in an agroecosystem in the southeast of Buenos Aires Province (General Pueyrredon District) during the non-breeding period, controlling the sex of the individuals studied. The digestive tract of 22 individuals captured outside their roost was analyzed. Frequency of occurrence and relative frequency were estimated for each food item. In addition, the availability of preys in the environment was estimated by using light traps. Diet composition analysis revealed the presence of seven orders of insects: Diptera and Lepidoptera presented the highest frequency of occurrence (95% and 91%, respectively), followed by Hemiptera (45%), Coleoptera (36%), Neuroptera (18%), and to a lesser extent, Trichoptera (9%), and Hymenoptera (4.5%). Regarding relative frequency, 60% of the diet composition of T. brasiliensis was represented by Diptera and Lepidoptera, and when the Hemiptera and Coleoptera orders were added, it escalated up to 90%. No significant differences were found in the diet composition between males and females. All orders of insects found in the diet of T. brasiliensis were recorded in the environment, including lepidopteran and hemipteran species that are considered harmful to crops. Given that these orders are part of the diet composition of T. brasiliensis, the potential of these mammals as biological controls of crop pests becomes evident.